Building a place for the student in his/her passage to first year of university life (Praxis Educativa, 2012)
This article seeks to share interpretations of the data collected on the characteristics of young people entering the first year with the aim of recognizing psychosocial aspects of the same for the purpose of identifying changes that occur during the first year of the course. Interest primarily to account for how the provisions are built up to action of habitus own university, which involve changes in the way to perceive, appreciate and act other than their own secondary education level. Work allows enabling and constraining recognize aspects in the transition from first year, as well as, issues relating to changes in the shares of a university habitus.
Keywords: students; university; habitus; schemes; young